Molecular identification of Salmonella enterica subsp enterica serovar Gallinarum biovars Gallinarum and Pullorum by a duplex PCR assay - Alves Batista, Diego Felipe [UNESP]; Freitas Neto, Oliveiro Caetano de; Almeida, Adriana Maria de [UNESP]; Barrow, Paul Andrew; Barbosa, Fernanda de Oliveira [UNESP]; Berchieri Junior, Angelo [UNESP] (Sage Publications Inc, 2016)
Salmonella enterica subsp. enterica serovar Gallinarum biovar Gallinarum (S. Gallinarum) and biovar Pullorum (S. Pullorum) are 2 poultry pathogens that cause major economic losses to the poultry industry worldwide. Control of both diseases mainly relies on the adoption of biosecurity programs, and success is dependent on accurate and fast detection. Based on this concept, we developed a duplex PCR assay, targeting 2 chromosomal sequences, which allowed us to precisely identify and differentiate S. Gallinarum and S. Pullorum field strains. This assay was validated by testing genomic DNA from 40 S. Gallinarum and 29 S. Pullorum field strains, 87 other Salmonella serovars, and 7 non-Salmonella strains. The serovar identifier region (SIR) primers produced a fragment only in S. Gallinarum and S. Pullorum strains, whereas the fragment from the ratA coding sequence, which was previously demonstrated to differentiate the 2 biovars, was also amplified from other Salmonella serovars. Our results showed that the combination of both SIR and ratA amplifications could be used to identify as well as to differentiate colonies of S. Gallinarum and S. Pullorum reliably. Thus, we believe this methodology can be a useful ancillary tool for routine veterinary diagnostic laboratories by providing rapid, accurate results.
Keywords: Duplex PCR; fowl typhoid; pullorum disease; Salmonella Gallinarum; Salmonella Pullorum